The Diversity of Trajectories of Large Housing Estates in Madrid, Spain. - Uceda, Pedro; Sorando, Daniel; Leal, Jesús (Springer Open, 2018)
Public and private housing developments between 1940 and 1990 shaped the City of Madrid by differentiating urban area types according to social composition, location and development type. Spanish housing policies over these decades fostered public housing stock that, unlike in European cities, ended up being transformed into owned rather than rented homes; closely linking certain disadvantaged groups to the most vulnerable areas of the city. In the chapter, current processes of physical and social vulnerability are analysed using data from the 2001 and 2011 Population and Housing Censuses using a multivariate analysis. The analysis differentiates between two stages of social housing estates in Madrid (under Francoism and in the democratic period) and private housing developments. These analyses show significant differences both in the trajectories of each of the types analysed in relation to contemporary vulnerability processes, as well as in the composition of the population that resides in them. Lastly, we examine challenges and proposals for the future of these urban areas, considering their social composition and the urban policies that seek to rebalance Madrid s neighbourhoods and paying attention to the insertion of the immigrant population into the most vulnerable neighbourhoods of the city.
Keywords: Wohnungswesen; Wohnsiedlung; Wohnungspolitik; Sozialwohnung; Stadtentwicklung; Fallbeispiel; Sozialraum